Dysregulated tryptophan metabolism contributes to metabolic syndrome in Chinese community-dwelling older adults - Shujing Sun; Fangting Hu; Yanru Sang; Sheng Wang; Xuechun Liu; Jiafeng Shi; Hongjuan Cao; Fangbiao Tao; Kaiyong Liu (BMC Endocrine Disorders)
Abstract Background As the prevalence of metabolic syndrome (MetS) rises among older adults, the associated risks of cardiovascular diseases and diabetes significantly increase, and it is closely linked to various metabolic processes in the body. Dysregulation of tryptophan (TRP) metabolism, particularly alterations in the kynurenine (KYN) and serotonin pathways, has been linked to the onset of chronic inflammation, oxidative stress, and insulin resistance, key contributors to the development of MetS. We aim to investigate the relationship between the TRP metabolites and the risk of MetS in older adults. Methods Ultra-performance liquid chromatography tandem mass spectrometry was used to detect TRP and its seven metabolites in a study involving 986 participants. Physical examination included the following indicators: blood pressure, body mass index, triglyceride levels, and high-density lipoprotein cholesterol (HDL-C) levels. Multiple linear regression, restricted cubic spline curve, binary logistic analysis, and sex-stratified analysis were used to explore the relationship between the metabolites and the risk of MetS in older adults. Results The results indicated that, after adjusting for covariates, higher levels of TRP, KYN, kynurenic acid (KA), and xanthurenic acid (XA) were risk factors for MetS (P for trend < 0.05). By contrast, higher ratios of 5-hydroxytryptamine to TRP and indole-3-propionic acid to TRP were protective factors against MetS (P for trend < 0.05). Conclusions TRP and its metabolites may serve as potential indicators for assessing and managing MetS in older adults, complementing existing biomarkers. Clinical trial number Not applicable.